OBLIGATIONS OF LAND RIGHTS HOLDERS TO MANAGE THEIR OWN AGRICULTURAL LAND - Suhartono Suhartono; Rahmatul Hidayati; Ahmad Siboy (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Agricultural land is a strategic asset in national development because it plays a direct role in maintaining food security and community welfare. However, the process of urbanization, industrialization, and weak legal supervision has led to massive land conversion and an increase in absentee land ownership practices (guntai). Landowners who do not manage their land directly cause a lot of land to become unproductive, illegally transferred, or used as an object of price speculation. This condition causes inequality in land distribution and hinders the goal of agrarian reform as mandated by the UUPA. Therefore, this study examines in depth the